A comprheensive review of Visual Programming Tools for Arduino - Melo, Julio; Fidelis, Melquiades; Alves, Sidney; Freitas, Ulisses; Dantas, Rummenigge (Proceedings (Brazilian Robotics Symposium. Online), 2020)
This document presents a systematic review of Visual Programming Tools for the Arduino Board. The Arduino board is an embedded platform that focus on enabling an easy way to teach embedded systems, but, due to its success, it ended up being used in different teaching levels, ranging from primary to university. The board was also applied in the teaching of robotics and other contexts since it is relatively cheap, easy to program and its community has produced a considerable amount of free educational material. Even though Arduino is a success it is still maturing in terms of educational purposes, aside the electronic knowledge that needs to be explored, the board is programmed, by default, with c++, which is considered not friendly to Computer Thinking beginners. Trying to solve this problem, many solutions apply Visual Programming, which is proven to make it easy for unexperienced and even children to learn the basis of Computational Thinking, in the educational context with Arduino. Even though there are many solutions applying visual programming for Arduino, there are no systematic review or survey on this subject, meaning that it is hard to identify where are the gaps and which are the problems that are already solved. Therefore, on this paper, it was performed a systematic review on the subject, the method found 372 papers, which 31 were selected for full review. The reviewed solutions where discussed and categorized, we expect that the presented results could be used as guideline for new research in the area and by educators and companies that are looking for visual programming tools for the Arduino board.